Fabrication and characterization of protein-based tissue scaffold - Ko, Kok Wei. (2011)
Silk has recently been exploited as a potential scaffold biomaterial for cell culture and tissue engineering applications, due to its good biocompatibility and physical properties. Thus, in the project, the properties of silk fibroin (SF) scaffold were investigated based on the changes in the SF concentration. The SF scaffolds were prepared and fabricated via freeze drying method for five different sets of SF concentration - (5, 7.5, 10, 12.5, 15%) wt/wt. They were then characterized to investigate its biological properties through various tests. The pore sizes and the porosity were found to decrease as SF concentration increased, which results in poorer cell attachment and migration within the scaffold. The swelling ratio/water uptake of the SF scaffold, which suggests the ability to absorb and hold the nutrients within the matrices, was also found to decrease with increasing SF concentration. The mechanical results showed that the compressive modulus increase with increasing SF concentration, which indicates a better mechanical strength to endure physiological loads and stresses. Thermal and structural analysis of the silk was done using the differential scanning calorimeter (DSC) and the fourier transform infrared (FTIR) spectrometer respectively. It was observed that the change in SF concentration does not affect the melting and crystallization behaviours of silk. And the spectra recorded from the structural analysis indicated the presence of secondary structures (α-helices and β-sheets) in amide I, II, III regions of protein. The SF scaffolds were tested for cytotoxicity towards the growth and morphology of fibroblast cells. It was found that there were no morphological changes and significant difference in the relative cell viability between the control and the scaffold extracts. Thus, concluding that the SF scaffolds did not induce cytotoxic reactivity.